2013
DOI: 10.1200/jco.2013.31.15_suppl.629
|View full text |Cite
|
Sign up to set email alerts
|

Double-blind, randomized, parallel group, phase III study to demonstrate equivalent efficacy and comparable safety of CT-P6 and trastuzumab, both in combination with paclitaxel, in patients with metastatic breast cancer (MBC) as first-line treatment.

Abstract: 629 Background: CT-P6(C) is an anti-HER2 MoAb, a biosimilar to trastuzumab (T). This trial is a global phase III study to compare C with T, both in combination with paclitaxel (P) as first-line treatment in women with HER2+ MBC. Methods: 475 patients with centrally confirmed HER2+ MBC were randomized to receive either C+P (n=244) or T+P (n=231). Patients had to have a baseline LVEF ≥50% and no history of serious cardiac disease. Study medication was as follows: C or T 8 mg/kg i.v. (day 1), followed by 3-weekl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
21
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 25 publications
(21 citation statements)
references
References 0 publications
0
21
0
Order By: Relevance
“…99 Published data from a study in patients with HER2 þ MBC showed comparability between CT-P6 and trastuzumab, each treatment in combination with paclitaxel, with respect to ORR and the incidence of adverse events. 86 Results from a trial comparing the efficacy of Hercules/Myl-1401O versus trastuzumab, each in combination with paclitaxel or docetaxel, as first-line treatment in patients with HER2 þ MBC showed equivalence in efficacy and comparable safety (Table 3). 89 Reported 24-week ORR was 69.6% (160 patients) in the Hercules/Myl-1401O group and 64.0% (146 patients) in the trastuzumab group, and the incidence of patients with at least 1 treatment-emergent adverse event was 96.8% (239 patients) in the Hercules/Myl-1401O group and 94.7% (233 patients) in the trastuzumab group.…”
Section: Kimberly Blackwell Et Almentioning
confidence: 99%
“…99 Published data from a study in patients with HER2 þ MBC showed comparability between CT-P6 and trastuzumab, each treatment in combination with paclitaxel, with respect to ORR and the incidence of adverse events. 86 Results from a trial comparing the efficacy of Hercules/Myl-1401O versus trastuzumab, each in combination with paclitaxel or docetaxel, as first-line treatment in patients with HER2 þ MBC showed equivalence in efficacy and comparable safety (Table 3). 89 Reported 24-week ORR was 69.6% (160 patients) in the Hercules/Myl-1401O group and 64.0% (146 patients) in the trastuzumab group, and the incidence of patients with at least 1 treatment-emergent adverse event was 96.8% (239 patients) in the Hercules/Myl-1401O group and 94.7% (233 patients) in the trastuzumab group.…”
Section: Kimberly Blackwell Et Almentioning
confidence: 99%
“…Four other biosimilars (CT-P6, MYL-1401O, SB3, and PF-05280014) have been approved by the FDA and EMA and have been shown to be similar to trastuzumab RP in confirmatory clinical studies (Table 3) [26,[33][34][35][36][37][38]. While all four biosimilars were evaluated with the recommended equivalence trial design, the patient population and primary endpoints in these studies differed from those used in the ABP 980 studies.…”
Section: Clinical Evidence From Other Trastuzumab Biosimilarsmentioning
confidence: 99%
“…In these five trials, anthracycline/taxanebased chemotherapy was used in the neoadjuvant setting and taxane-based chemotherapy in the metastatic setting; no significant differences between the biosimilar trastuzumab and the trastuzumab RP were reported. The trials evaluating MYL-1401O, PF-05280014, and CT-P6 were conducted in HER2-overexpressing MBC; the primary endpoint in all three trials was ORR (the prespecified equivalence margin was ± 15%) [33,35,37]. As discussed earlier, MBC is a less sensitive and less homogenous population to demonstrate clinical equivalence of a biosimilar trastuzumab, and ORR is not the preferred primary endpoint since it is associated with a larger uncertainty in long-term efficacy outcomes.…”
Section: Clinical Evidence From Other Trastuzumab Biosimilarsmentioning
confidence: 99%
See 1 more Smart Citation
“… 50 The potential biosimilar mAb CT-P6 (Celltrion) has demonstrated similarity to trastuzumab in pharmacokinetic and safety profile analyses, and comparable response rates in patients with HER2-overexpressing metastatic breast cancer in combination with paclitaxel. 52 …”
Section: Biosimilars In Developmentmentioning
confidence: 99%